(untitled) (International Journal of Environmental Sciences, 2025)
Graphs considered here are simple, finite, connected and undirected. The vertex set and edge set of a graph are and respectively. The concept of cordial labeling was introduced by Cahit in the year 1987. The concept of mean labeling was introduced by S. Somasundaram and Raja Ponraj. The concept of power mean labeling was introduced by P. Mercy and S. Somasundaram. Motivated by above concepts, we introduced a new type of labeling called power mean cordial labeling.